The influence of thermal motion of particles on the formation of cavities in plasma - Azarenkov, N.A.; Chibisov, A.D.; Chibisov, D.V. (Problems of Atomic Science and Technology, 2022)
The effect of the thermal motion of ions and electrons on the formation of plasma density cavities which appear due to inhomogeneous stochastic electric fields is considered. Using the equation of motion of plasma particles in a constant magnetic field and in an inhomogeneous stochastic electric field with a frequency of the order of lower hybrid oscillations, taking into account the thermal motion of particles, the diffusion coefficients and drift velocities of ions and electrons are obtained. These values are used in the Fokker-Planck equation to determine the stationary distribution of the plasma density due to the effect of an inhomogeneous stochastic electric field. The conditions for the thermal velocities of particles under which the formation of a cavity is possible are obtained.